2020
DOI: 10.1016/j.jsb.2020.107507
|View full text |Cite
|
Sign up to set email alerts
|

The shell matrix and microstructure of the Ram’s Horn squid: Molecular and structural characterization

Abstract: Molluscs are one of the most diversified phyla among metazoans. Most of them produce an external calcified shell, resulting from the secretory activity of a specialized epithelium of the calcifying mantle. This biomineralization process is controlled by a set of extracellular macromolecules, collectively defined as the organic matrix. In spite of several studies, these components are mainly known for bivalve and gastropod classes. In the present study, we investigated the physical and biochemical properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 93 publications
(116 reference statements)
1
25
0
Order By: Relevance
“…The resolved and less crowded aromatic region peaks (e.g., 129 ppm) suggest the occurrence of the aromatic amino acids (e.g., tyrosine) while the broad peak centered at 72 ppm may arise from either hydroxyprolines and/or polysaccharides. Different from A. hians, the bio-organic content of the AIM of the shell of S. spirula (Figure S3c)-another member of the cephalopod class-was shown as being dominated by chitin and possibly other oligosaccharides with only a minor proteinaceous content [28]. For comparison we also show the 13 C CPMAS spectrum of the AIM of Arctica islandica (Figure S3b)-a bivalve whose shell acid insoluble matrix is protein-rich (~90:10 proteins versus saccharides) [29].…”
Section: Solid State Nuclear Magnetic Resonancementioning
confidence: 88%
See 1 more Smart Citation
“…The resolved and less crowded aromatic region peaks (e.g., 129 ppm) suggest the occurrence of the aromatic amino acids (e.g., tyrosine) while the broad peak centered at 72 ppm may arise from either hydroxyprolines and/or polysaccharides. Different from A. hians, the bio-organic content of the AIM of the shell of S. spirula (Figure S3c)-another member of the cephalopod class-was shown as being dominated by chitin and possibly other oligosaccharides with only a minor proteinaceous content [28]. For comparison we also show the 13 C CPMAS spectrum of the AIM of Arctica islandica (Figure S3b)-a bivalve whose shell acid insoluble matrix is protein-rich (~90:10 proteins versus saccharides) [29].…”
Section: Solid State Nuclear Magnetic Resonancementioning
confidence: 88%
“…An additional advantage is its ability to identify the structural forms of the calcareous inorganic matrix-crystalline and/or amorphous-and interactions with the bioorganics. [28,29]. 13 C, 31 P Magic Angle Spinning (MAS) NMR measurements were carried out on 300 MHz solid state NMR Bruker AVANCE III spectrometer using a 4 mm triple-resonance MAS NMR probe with zirconia rotors.…”
Section: Solid State Nuclear Magnetic Resonance (Ssnmr)mentioning
confidence: 99%
“…The presence of housekeeping proteins in the shell matrix is not surprising, although it is intriguing because no study has addressed what they are doing there. Housekeeping proteins have also been reported to be present in the shell matrix of Crassostrea angulata and C. hongkongensis (Upadhyay et al 2016), Euhadra quaesita (Shimizu et al 2019), and Spirula spirula (Oudot et al 2020a).…”
Section: Identification Of Shared Proteins Between the Shell Of Conchiferans And The Eggcase Of The Argonautsmentioning
confidence: 99%
“…Because of the absence of EGF-ZP, the eggcase of the Argonauts lacks the nacreous layer, and is composed of only calcite. However, Oudot et al (2020a) analyzed the coiled shell of the Spirulid Spirula spirula, and found that the species shares only a few similarities with known SMPs of the Mollusks.…”
Section: Absence Of Major Smps In the Cephalopodsmentioning
confidence: 99%
“…Although live observations of Spirula are very rare, there have been important advances in our understanding of its shell structure and function [11,12], life history and biogeography [13,14] and phylogeny and systematics [15][16][17]. Still, live observations offer researchers a unique opportunity to directly examine the behavioral responses of organisms about which behavior otherwise has to be merely surmised.…”
mentioning
confidence: 99%